Interpretation of coronary steal syndrome and haemodynamic changes after surgical closure of coronary fistula using Doppler wire and computational fluid dynamics analysis: a case report. Issue 4 (24th April 2021) - Lee, Kwan Yong; Chang, Kiyuk; Lee, Joo Myung; Lee, Sang-Wook
Abstract: Background: Coronary arteriovenous fistulas (CAFs) are rare but can cause myocardial ischaemia and other complications. However, the haemodynamic and physiologic characteristics of significant CAFs requiring treatment are poorly described. We report a case of CAF causing coronary steal syndrome in which haemodynamic changes were assessed before and after surgical closure using a Doppler wire and computational fluid dynamics (CFD) technique. Case summary: A 51-year-old woman presented with exertional chest pain for 3 years. Progressive dyspnoea occurred with exertion. Treadmill and cardiopulmonary exercise tests showed suspicious myocardial ischaemia. Coronary angiography and contrast-enhanced coronary computed tomography angiography (CCTA) revealed a coronary fistula arising from the distal left main coronary artery that drained into the pulmonary artery trunk. We observed a persistent coronary steal phenomenon at baseline and during hyperaemia and a systolic dominant flow rate pattern inside the CAF by Doppler wire-based flow rate measurement. According to CFD analysis based on CCTA, low wall shear stress and a high focal oscillatory shear index were observed at the ostial sites of aneurysmal sacs in the CAF. After successful surgical closure of the CAF, the vessel sizes and flow rate distributions of the coronary arteries increased. Discussion: Doppler wire-based flow rate distribution measurements and CFD analysis may facilitate the identification of significant coronary steal syndrome requiring closure and the evaluation of future risks of life-threatening complications such as thrombosis and rupture.